Evaluating the relationship between deposition and layer quality in large-scale additive manufacturing of concrete. Issue 2 (3rd April 2019) - Ashrafi, Negar; Duarte, Jose Pinto; Nazarian, Shadi; Meisel, Nicholas A.
ABSTRACT: Scaling up additive manufacturing (AM) for automated building construction requires expertise from different fields of knowledge, including architecture, material science, engineering, and manufacturing to develop processes that work for practical applications. While concrete is a viable candidate for printing due to its common use in building, it raises important challenges in deposition due to the material deformation that occurs as concrete transitions from fresh to hardened states. This study aims to experimentally quantify the deformation of printed concrete layers under the influence of different processing variables, including layer thickness, printing orientation, and direction. A mixer-pump extrudes the material and an industrial 6-axis robotic arm, which provides various ranges of movement in different axes, layers the material. The results of this study can be used to develop a tool for predicting and accounting for the deformation of concrete layers during the AM process.